Strengthening the Original Democracy of The Village in North Baumata Village, Taebenu District – Kupang Regency - JACOB, Ananias Riyoan Philip; HUMAU, Frans B. R; TRIADMAJA, Stefanus (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
By strengthening local democracy, this community service project aims to promote all-encompassing village development. The program's main goals are to increase community involvement in village decision-making and local governments' capacity to uphold democratic norms. Through a range of activities, including as training, group discussions, and mentorship, the village community is encouraged to participate more actively in the creation and implementation of village Ensuring the participation of marginalized groups, including women, youth, and individuals with disabilities, is a crucial step in implementing an inclusive strategy.  This approach is expected to result in more fair and sustainable village development through more accountability, transparency, and wider participation in the village government process. It is hoped that other villages in the region would be able to promote participatory democracy by taking a cue from this initiative. Several speakers from Cendana University's Political Science Study Program participated in this community service program, which was held in North Baumata Village, Taebenu District, Kupang Regency.